Geographic distribution analysis of the genus Xenodacnis (Birds: Thraupidae) using ecological niche modeling - Aguilar, Juan M. (2019)
Xenodacnis is a monotypic thraupid genus restricted to the tropical high Andes of Peru and Ecuador. Its only species, X. parina has a large discontinuous distribution from central Ecuador to southern Peru. To date, three subspecies are recognized, all separated by geographical barriers that clouded promote allopatric events. The taxonomic affinities of the Ecuadorian population have not been assessed since its discovery in the 1970s at the Cajas National Park in Azuay province. I studied the environmental affinities between the distribution of the described subspecies and the Ecuadorian population bias ecological niche modeling. I found a distinctive ecological niche in the distribution of each of the analyzed populations and also for the southern Arequipa population. These different environmental niche conditions come apart by deep Andean valleys playing a role as geographical barriers for the isolation of these populations that need further taxonomic analysis.